Experimental and theoretical analysis of Nnanotransport in oligophenylene dithiol junctions as a function of molecular length and contact work function - Xie, Zuoti; Bâldea, Ioan; Smith, Christopher E.; Wu, Yanfei; Frisbie, C. Daniel (ACS nano, 2015)
We report the results of an extensive investigation of metal-molecule-metal tunnel junctions based on oligophenylene dithiols (OPDs) bound to several types of electrodes (M1-S-(C6H4)n-S-M2, with 1 ≤ n ≤ 4 and M1,2 = Ag, Au, Pt) to examine the impact of molecular length (n) and metal work function (Φ) on junction properties. Our investigation includes (1) measurements by scanning Kelvin probe microscopy of electrode work function changes (ΔΦ = ΦSAM - Φ) caused by chemisorption of OPD self-assembled monolayers (SAMs), (2) measurements of junction current-voltage (I-V) characteristics by conducting probe atomic force microscopy in the linear and nonlinear bias ranges, and (3) direct quantitative analysis of the full I-V curves. Further, we employ transition voltage spectroscopy (TVS) to estimate the energetic alignment εh = EF - EHOMO of the dominant molecular orbital (HOMO) relative to the Fermi energy EF of the junction. Where photoelectron spectroscopy data are available, the εh values agree very well with those determined by TVS. Using a single-level model, which we justify via ab initio quantum chemical calculations at post-density functional theory level and additional UV-visible absorption measurements, we are able to quantitatively reproduce the I-V measurements in the whole bias range investigated (∼1.0-1.5 V) and to understand the behavior of εh and Γ (contact coupling strength) extracted from experiment. We find that Fermi level pinning induced by the strong dipole of the metal-S bond causes a significant shift of the HOMO energy of an adsorbed molecule, resulting in εh exhibiting a weak dependence with the work function Φ. Both of these parameters play a key role in determining the tunneling attenuation factor (β) and junction resistance (R). Correlation among Φ, ΔΦ, R, transition voltage (Vt), and εh and accurate simulation provide a remarkably complete picture of tunneling transport in these prototypical molecular junctions.
Gesehen am 30.06.2020